Wakaf & Kesejahteraan Umat ( Filantropi Islam yang Hampir Terlupakan) - Drs. H. Farid Wadijdy, M.Pd., Mursyid, M.SI. (Pustaka Pelajar, 2007)
Wakaf & Kesejahteraan Umat ( Filantropi Islam yang Hampir Terlupakan)